PENDIRIAN PERPUSTAKAAN DESA UNTUK PENINGKATAN LITERASI MASYARAKAT DESA BAWU BATEALIT JEPARA - Rohman, Fathur; Farida, Yushinta Eka; Muslih, Muhammad; Ilham, Rizahul (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article aims to describe a community service program by establishing a village library to increase the literacy of the people of Bawu village, Batealit, Jepara. There are two problems studied in this paper, namely 1) How to establish a village library to increase the literacy of the Bawu village community? 2) what are the results of the program? This program is implemented using the Participatory Rural Appraisal (PRA) method with stages: a) problem identification b) planning c) implementation d) monitoring e) evaluation. The result of this program was the establishment of the Bawu Batealit Jepara village library, which was named the "Balai Pintar" library. This library is located in the office complex of Bawu officials and has a collection of 270 book titles. The existence of this new library has been quite successful in attracting public interest, especially elementary school-age children, in reading. The monitoring results, it was found that the average number of library visitors every day is around 15-20 people.